Peran Pemerintah dalam Mengoptimalkan Dinamika Wirausaha: Mendukung Kemajuan Ekonomi Indonesia Khususnya Wilayah Jakarta - Ciek Julyati Hisyam; Kailla Putri Aisyah; Siti Umi Khoiriah; Syafaa Marwah Augea (Trending: Jurnal Manajemen dan Ekonomi, 2024)
This research analyzes the dynamics of entrepreneurship in Jakarta using theoretical concepts from Pierre Bourdieu, especially the concepts of "arena", "capital", and "habitus". Through this research, we identified Jakarta government programs that support the growth of the entrepreneurial ecosystem, analyzed the challenges faced by Jakarta entrepreneurs, and evaluated the government's strategy in overcoming these challenges. Focusing on the Jakpreneur program and other initiatives, we found that while government efforts have increased accessibility and support for entrepreneurship, challenges remain such as bureaucratic complexity, limited access to capital, and inadequate infrastructure. The government's strategy to overcome these challenges includes providing infrastructure, digitizing public services, empowering MSMEs, supporting technology and innovation, and paying attention to environmental aspects. The implication of this research is the importance of collaboration between the government, private sector and society in building a dynamic and growing entrepreneurial environment, as well as providing a positive impact on the economic growth of Jakarta and Indonesia as a whole.